Epistemology of Value Education: Cultivating Humanist Character in Students from a Contemporary Education Perspective - Ayu Rizkia Silviana; Mukh Nursikin (Journal of Innovative and Creativity, 2025)
Education is a fundamental aspect that plays a significant role in the change and progress of a society. As a strategic element in creating a more dignified civilization, education not only functions as a transfer of knowledge but also as a means to instill character values and build noble morals in students. This research aims to examine the implementation of value education epistemology in the context of contemporary Islamic education, with an emphasis on instilling humanist character in students. This research uses a qualitative method with the type of library research by analyzing written literature in the form of books and scientific journals related to the research theme. The results show that humanist character education in Islam requires educators as role models in fostering noble values, such as compassion, social responsibility, and religious awareness. The method used in instilling character values involves the strategies of moral knowing, moral modeling, moral feeling, moral acting, and giving advice and habituation. Value education in Islam aims to create people who are not only intellectually intelligent but also have noble character and are responsible for their role in the world. In facing the challenges of modernization and globalization, Islamic education must respond to these needs by integrating spiritual, moral, and social aspects while contributing to developing a moral civilization. This study concludes that to build a complete human being (Insan Kamil), humanist character education needs to be applied holistically in everyday life in schools, families, and communities.